Waist‐to‐height ratio and cardiometabolic risk factors in adolescence: findings from a prospective birth cohort. Issue 5 (25th July 2013) - Graves, L.; Garnett, S. P.; Cowell, C. T.; Baur, L. A.; Ness, A.; Sattar, N.; Lawlor, D. A.
Summary What is already known about this subject In adults, associations between body mass index (BMI), waist‐to‐height ratio (WHtR) and cardiometabolic outcomes are similar. In children and adolescents, results from cross‐sectional studies examining the associations between BMI z scores, WHtR and cardiometabolic outcomes are conflicting and there is a paucity of prospective data. What this study adds This is the first study to demonstrate the prospective association between WHtR in childhood and cardiometabolic outcomes in adolescent boys. WHtR is a simple calculation that can be used to identify children and adolescents for cardiometabolic risk without the need for reference growth charts. The WHtR cut‐point of ≥0.5 was highly specific in identifying cardiometabolic risk co‐occurrence but has poor sensitivity. Objective To examine the associations between body mass index (BMI) and waist‐to‐height ratio (WHtR) measured in childhood and adolescence and cardiometabolic risk factors in adolescence. Methods Secondary data analysis of the Avon Longitudinal Study of Parents and Children, a population based cohort. Data from 2858 adolescents aged 15.5 (standard deviation 0.4) years and 2710 of these participants as children aged 7–9 years were used in this analysis. Outcome measures were cardiometabolic risk factors, including triglycerides, low density lipoprotein cholesterol, high density lipoprotein cholesterol, insulin, glucose and blood pressure at 15 years of age. Results Both BMI and WHtR measured at ages 7–9 years and at age 15 years were associated with cardiometabolic risk factors in adolescents. A WHtR ≥0.5 at 7–9 years increased the odds by 4.6 [95% confidence interval 2.6 to 8.1] for males and 1.6 [0.7 to 3.9] for females of having three or more cardiometabolic risk factors in adolescence. Cross‐sectional analysis indicated that adolescents who had a WHtR ≥0.5, the odds ratio of having three or more cardiometabolic risk factors was 6.8 [4.4 to 10.6] for males and 3.8 [2.3 to 6.3] for females. The WHtR cut‐point was highly specific in identifying cardiometabolic risk co‐occurrence in male children and adolescents as well as female children (90 to 95%), but had poor sensitivity (17 to 53%). Similar associations were observed when BMI was used to define excess adiposity. Conclusions WHtR is a simple alternative to age and sex adjusted BMI for assessing cardiometabolic risk in adolescents.